ASSESSMENT OF ANTHROPOGENIC POLLUTION OF SOILS IN CHERNIVTSI (UKRAINE) BY MAGNETIC SUSCEPTIBILITY AND HEAVY METAL CONTENT - Bondar, K.; Sachko, A.; Tsiupa, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper is devoted to spatial distribution of low-frequency magnetic susceptibility (χ) of surface sediments in Chernivtsi city as an informative indicator of geochemical contamination of the topsoil. The bulk content of heavy metals in urban soils and the correlations between the χ, frequency dependence of magnetic susceptibility (kfd) and the content of Cd, Mn, Cu, Ni, Pb, Zn were studied. Χ vary from 10∙10-8 to 1286∙10-8 m3 /kg with a median value of 66∙10-8 m3 /kg. In 20 % of samples χ exceeds the median value three times or more, indicating that the soil is contaminated with iron dust and magnetic particulate matter derived from anthropogenic aerosols. Priority contaminants of city soils are metals such as Pb and Zn, the bulk content of which exceeds the trigger concentration in the vast majority of samples. The χ revealed strong correlation with bulk content of Pb and Zn and the weaker one, but still statistically significant, with Cu and Cd. An additional criterion for the common anthropogenic origin of heavy metals and magnetic minerals in soils is the significant negative correlation coefficients between kfd and content of Zn, Pb, and Cu. So, it can be argued that the increase in Zn, Pb, and Cu content is accompanied by an increase in concentration of magnetic minerals in the multidomain state. The maps were produced, showing spatial distribution of χ and Pollution Load Index (PLI), calculated by three metals (Zn, Pb, and Cu). For 51 % of the samples, the PLI indicates no contamination, 35 % indicate moderate contamination,14 % are strongly contaminated. These results prove that surface sediment over a large area of the city require measures to reduce their toxicity. The correlation coefficient between χ and PLI makes 0.88, indicating χ as a quick indicator of geochemical soil contamination in the city of Chernivtsi.
Keywords: soil; magnetic susceptibility; heavy metals; Pollution Load Index; Chernivtsi